Effects of electroporation on Acanthamoeba Polyphaga - Pessoa, Palloma Santiago Prates; Barcelos, Raphael; Pinto, Larissa Fagundes; de Freitas, Denise; Campos, Mauro (PLOS ONE, 2025)
Background Species of the genus Acanthamoeba spp. are ubiquitous and can cause Acanthamoeba keratitis (AK), a serious corneal infection. Due to the toxicity and ineffectiveness of currently available prolonged therapies, we investigated electroceutical treatment aimed at facilitating the permeation of molecules through the membrane of cysts and trophozoites, which allows for faster elimination of the parasite. Methods Cysts and trophozoites of Acanthamoeba polyphaga (ATCC® 30461TM) were exposed in vitro to an electric field with intensities of 2,000 volts and 2,500 volts. Viability after electroporation was assessed by the exclusion method with 0.4% trypan blue dye, while permeabilization was assessed by fluorescence microscopy using propidium iodide (PI), since both are impermeable to the membrane of viable and intact cells. The images were acquired on a Nikon Eclipse TI-U microscope and analyzed using ImageJ software. Results With regard to viability, 40% of the trophozoites electroporated at 2,000 V and 42% of those electroporated at 2,500 V were lost, while for cysts the loss was 13% and 16% respectively. Considering permeabilization, 55% of trophozoites and cysts were permeabilized at 2,000 V (p ≤ 0.05); and 59% at 2,500 V for both (p ≤ 0.05). Values of p < 0.05 were considered statistically significant. Conclusion The voltages tested were effective for both cysts and trophozoites, since the percentages of permeabilization were close, with no statistical significance between them, only with the control groups. These results suggest the possibility that an electroceutical treatment could be applied as a complement to the standard treatment for AK.